The validity and reliability of a smartphone application for measuring wrist and metacarpophalangeal joint motion - Özçelep, Ömer Faruk; Yavuzer, Melek Güneş; Tunalı, Ayşe Nur (My University, 2024)
Background Accurate measurement of the range of motion (ROM) is crucial for guiding upper extremity rehabilitation. Inaccurate measurements can mislead clinicians and harm patient compliance. This study aimed to evaluate the validity and reliability of a smartphone application (Angulus) for measuring wrist and metacarpophalangeal (MCP) joint ROM. Methodology This study included 64 volunteers with no prior wrist injuries. The wrist flexion/extension, radial/ulnar deviation, and MCP joint flexion/extension ROM were assessed by an experienced physiotherapist (Assessor 1) using the Angulus and a standard two -arm goniometer. The validity of Angulus was evaluated by correlating it with the goniometer measurements using the Pearson correlation coefficient. For the reliability analysis, an inexperienced biomedical engineer (Assessor 2) performed the same measurements using Angulus twice in different sessions, in addition to Assessor 1. The intra-rater and inter -rater reliability were tested using the intraclass correlation coefficient. Results The mean age of the participants was 29.5 +/- 8.2 years, with 62% being female. The validity of the Angulus app measurements was indicated by the adequate to excellent correlation between the Angulus and goniometer measurements (ranging from 0.44 to 0.81). The intra-rater reliability of the Angulus app was excellent for Assessor 1 (ranging from 0.76 to 0.90) and adequate to excellent for Assessor 2 (ranging from 0.71 to 0.88). The inter -rater reliability of Angulus was excellent (ranging from 0.91 to 0.96). Conclusions Angulus is a valid and reliable method to measure the wrist and MCP joint ROM.
Keywords: Metacarpophalangeal Joint; Mobile Phone Application; Range Of Motion (Rom); Reliability And Validity; Wrist Evaluation